Influencing factors of efflorescence degree of cement-based decorative mortar. (February 2019) - Liu, X F; Peng, J H; Zhang, J X
Abstract: The cement-based decorative mortar is a kind of good finishing material with abundant shape and colour. But the colour aberration of surface efflorescence seriously hinders the further application of cement-based decorative mortar. In the paper, it is researched of quantitative analysis on effect of calcium hydroxide content and porosity on the efflorescence degree by the function of efflorescence degree and grey scales based on image processing technology. The results show that the efflorescence degree will heighten as the content of calcium hydroxide increases, and there is a safe value of mortar without efflorescence. The open porosity plays another decisive role in the efflorescence degree of mortar. The efflorescence degree of mortar increases with the increase of porosity, and the relationship between them is linear.